MOTIVASI BELAJAR, PRESTASI BELAJAR, DAN KEAKTIFAN SISWA DI KELAS DITINJAU DARI KEIKUTSERTAAN SISWA DALAM PROGRAM BIMBINGAN BELAJAR - Amelia, Retna Rizki; Nugraheni, Benedecta Indah (Jurnal Pendidikan Ekonomi dan Akuntansi, 2021)
This research aims to find out whether there are differences in learning motivation, learning achievement, and student’s activity in the classroom perceived from the participation of students in learning guidance course program. This research is a quantitative-comparative research which was conducted in Maret 2019. The population of this research were all students of SMA Negeri 7 Yogyakarta. The samples of this research were 240 students of the eleventh grade of SMA Negeri 7 Yogyakarta taken by using purposive sampling technique. Data were collected by using questionnaire and analyzed by using Independent Sample T-test. The result of this research shows: (1) there is difference in learning motivation from the participation of students in the learning guidance course program (sig.(2-tailed) = 0,011 0,05); (2) there is no difference in learning achievement from the participation of students in the learning course program (sig.(2-tailed) = 0,037 0,05). 0,104 0,05); (3) there is difference in student’s activity in the classroom perceived from the participation of students in the learning guidance course program (sig.(2-tailed) = 0,037 0,05).Keywords: learning motivation, learning achievement, student’s activity, learning guidance course program